Pengajaran Firman Secara Sehat menurut 1 Timotius 1:3-11 dan Implementasinya bagi Pengajar GKI “Galet” Niufmuti Kupang NTT - Victor Immanuel Rahardjo; Dwi Setio Budiono Santoso; Yandri Tana (Sekolah Tinggi Alkitab Jember, 2023)
This research exposes Paul's letter to his spiritual children in 1 Timothy 1:3-11. The method used is field qualitative. There is advice that is relevant for every teacher of God's word at GKI